Individual Mycobacterium tuberculosis Resuscitation-Promoting Factor Homologues Are Dispensable for Growth In Vitro and In Vivo - Tufariello, JoAnn M. (American Society for Microbiology, 2004)
Mycobacterium tuberculosis possesses five genes with significant homology to the resuscitation-promoting factor (Rpf) of Micrococcus luteus. The M. luteus Rpf is a secreted ∼16-kDa protein which restores active growth to cultures of M. luteus rendered dormant by prolonged incubation in stationary phase. More recently, the Rpf-like proteins of M. tuberculosis have been shown to stimulate the growth of extended-stationary-phase cultures of Mycobacterium bovis BCG. These data suggest that the Rpf proteins can influence the growth of mycobacteria; however, the studies do not demonstrate specific functions for the various members of this protein family, nor do they assess the function of M. tuberculosis Rpf homologues in vivo. To address these questions, we have disrupted each of the five rpf-like genes in M. tuberculosis Erdman, and analyzed the mutants for their growth in vitro and in vivo. In contrast to M. luteus, for which rpf is an essential gene, we find that all of the M. tuberculosis rpf deletion mutant strains are viable; in addition, all show growth kinetics similar to Erdman wild type both in vitro and in mouse organs following aerosol infection. Analysis of rpf expression in M. tuberculosis cultures from early log phase through late stationary phase indicates that expression of the rpf-like genes is growth phase-dependent, and that the expression patterns of the five M. tuberculosis rpf genes, while overlapping to various degrees, are not uniform. We also provide evidence that mycobacterial rpf genes are expressed in vivo in the lungs of mice acutely infected with virulent M. tuberculosis.